Issues of Improving the Legislation of Kazakhstan Aimed at Countering the Unauthorized Seizure of Land and Its Illegal Sale - ASHIRBEKOV, Marat; BEKISHEVA, Sabigul; NESSIPBAEVA, Indira; SOPYKHANOVA, Assel (Journal of Advanced Research in Law and Economics, 2019)
The relevance of the research is due to the fact that at present, both in Kazakhstan and around the world, there are changes and reforms in the social, economic and political spheres, which contributes to the growth of living standards of the population, generates demand and supply for products of a market economy. In this regard, the mechanisms for the protection of property rights require increased attention from the institutions of state power, the effectiveness and improvement of current legislation. The purpose of the study is to identify potential gaps, develop evidence-based proposals for improving legislation based on international standards and international experience. The main research methods of the studied problem were historical, comparative legal, statistical, empirical, analysis and comparison, which allowed to study the problem in more detail by identifying historical patterns, real state of affairs and identify the best solutions that can be implemented in the legislation of Kazakhstan. The presented research was carried out taking into account the land policy pursued by the authorized state bodies of Kazakhstan, public associations and interested parties, which resulted in the provision of reasonable proposals for amendments to the legislation regarding the prevention and prevention of unauthorized seizure of land and its illegal sale. The theoretical significance of the research is aimed at the scientific understanding of such a negative phenomenon as the unauthorized seizure of the earth. The practical significance of the study lies in the fact that the proposed provisions are aimed at improving the national legislation that contributes to minimizing and counteracting offenses in this area.